2012
DOI: 10.1109/jphot.2012.2188788
|View full text |Cite
|
Sign up to set email alerts
|

Stabilized Large Mode Area in Tapered Photonic Crystal Fiber for Stable Coupling

Abstract: A rigorous modal solution approach based on the numerically efficient finite element method has been used to design a tapered Photonic Crystal Fibre with a large mode area that could be efficiently coupled to an optical fiber. We report here for the first time that the expanded mode area can be stabilized against possible fabrication tolerances by introducing a secondary surrounding waveguide with larger air-holes in the outer ring. A full-vectorial H-field approach is employed to obtain mode field areas along… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1
1

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…2. There have been different definitions used to quantify this mode-size area, and for a Gaussian-shaped field profile, they give identical results [37]. The spot size, given as , can be defined as the area where the power density is higher than 1=e 2 of the maximum power density.…”
Section: Resultsmentioning
confidence: 99%
“…2. There have been different definitions used to quantify this mode-size area, and for a Gaussian-shaped field profile, they give identical results [37]. The spot size, given as , can be defined as the area where the power density is higher than 1=e 2 of the maximum power density.…”
Section: Resultsmentioning
confidence: 99%
“…6 by a dashed blue and a red solid lines, respectively. The mode size area or the effective area (A e f f ) can be given [23] by,…”
Section: Resultsmentioning
confidence: 99%
“…We have introduced a novel idea where by using different air-hole diameter in different rings and then reducing the PCF overall dimension, its spot-size can be increased, which would be suitable to cuple to a SMF and also will have better stability with the fabrication tolerances. The coupling efficiency of a specialised PCF with unequal air-holes [18] and with tradiational PCF with equal air-holes are shown in Fig.3 by solid and dashed curves when the pitch is continuously reduced. It can be observed that when specialized PCF is used, the coupling efficiency is higher and more stable with the PCF tapering.…”
Section: Resultsmentioning
confidence: 99%